First-in-man study with a novel PEGylated recombinant human insulin-like growth factor-I. (April 2017) - Kletzl, H.; Guenther, A.; Höflich, A.; Höflich, C.; Frystyk, J.; Staack, R.F.; Schick, E.; Wandel, C.; Bleich, N.; Metzger, F.
Abstract: Objective: This study is a first time assessment of safety and tolerability, pharmacokinetics, and pharmacodynamics of RO5046013 in human, in comparison with unmodified rhIGF-I. Design: The study was conducted as a single-center, randomized, double-blinded, placebo-controlled, single ascending dose, parallel group study in a clinical research unit in France. A total of 62 healthy volunteers participated in this clinical trial. RO5046013 was given as single subcutaneous injection, or as intravenous infusion over 48 h, at ascending dose levels. The active comparator rhIGF-I was administered at 50 μg/kg subcutaneously twice daily for 4 days. Safety and tolerability, pharmacokinetics, and pharmacodynamics of RO5046013 were evaluated. Results: PEGylation resulted in long exposure to RO5046013 with a half-life of 140–200 h. Exposure to RO5046013 increased approximately dose proportionally. RO5046013 was safe and well tolerated at all doses, injection site erythema after SC administration was the most frequent observed AE. No hypoglycemia occurred. Growth hormone (GH) secretion was almost completely suppressed with rhIGF-I administration, whereas RO5046013 caused only a modest decrease in GH at the highest dose given IV. Conclusions: PEGylation of IGF-I strongly enhances half-life, reduces the negative GH feedback and hypoglycemia potential, and therefore offers a valuable alternative to rhIGF-I in treatment of relevant diseases. Highlights: PEGylated IGF-I was tested for the first time in humans and was well tolerated. Strongly improved pharmacokinetic properties support once-a-week or less frequent dosing. Improved properties reduce acute side effects of IGF-I dosing.